Disparity in Child Custody Decisions from the Perspective of the Marriage Law and KHI - Ahdie Atid Dzikra; Kamarusdiana Kamarusdiana; Yassardin Yassardin (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
This research is a study that focuses on the disparity of decisions in child custody cases. The difference in decisions given by the Tangerang Religious Court in the same case. This study focuses on the factors in the granting of custody from the analysis and consideration of the panel of judges in case No. 967/Pdt.G/2014/PA.Tng and No. 2539/Pdt.G/2016/PA.Tng. The research method used is descriptive analysis. The factors that cause different decisions. In the first case the father as the defendant was unable to properly care for, educate and look after the child, and in the second case the mother as the respondent had left the applicant for more than two years and never returned. In the perspective of the law of marriage and the Compilation of Islamic Law (KHI)